2015
DOI: 10.1097/qad.0000000000000508
|View full text |Cite
|
Sign up to set email alerts
|

Broad and persistent Gag-specific CD8+ T-cell responses are associated with viral control but rarely drive viral escape during primary HIV-1 infection

Abstract: Objective We characterized protein-specific CD8+ T-cell immunodominance patterns during the first year of HIV-1 infection, and their impact on viral evolution and immune control. Methods We analyzed CD8+ T-cell responses to the full HIV-1 proteome during the first year of infection in eighteen antiretroviral-naïve individuals with acute HIV-1 subtype C infection, all identified prior to seroconversion. Ex vivo and cultured IFN-γ ELISPOT assays were performed and viruses from plasma were sequenced within defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(63 citation statements)
references
References 53 publications
(76 reference statements)
3
54
3
Order By: Relevance
“…As a result, the selective advantage for the virus to escape just one CTL response decreases [41], leading to slow escape. Consistent with this, a recent study showed that broad Gag responses are associated with few escapes and low viral load in HIV-1-infected individuals [42]. Thus, slow escape rates during chronic infections are to be expected for broad immune responses, and are not indicative of non-lytic or poor control by CTLs.…”
Section: Late Escape Ratesmentioning
confidence: 69%
“…As a result, the selective advantage for the virus to escape just one CTL response decreases [41], leading to slow escape. Consistent with this, a recent study showed that broad Gag responses are associated with few escapes and low viral load in HIV-1-infected individuals [42]. Thus, slow escape rates during chronic infections are to be expected for broad immune responses, and are not indicative of non-lytic or poor control by CTLs.…”
Section: Late Escape Ratesmentioning
confidence: 69%
“…Several mechanisms may be responsible for the greater reduction in primary infection. One possible explanation is the lack of escape CTL in the very early stage of infection (40,41). As recently reported by Deng and colleagues (41), CTL escape variants dominate the HIV reservoir of individuals starting ART during chronic but not acute infection; moreover, these CTL escape variants can be reactivated and released after latency reversal.…”
Section: Discussionmentioning
confidence: 82%
“…In addition, CTL may be more functional early in infection (40,42). Several studies have investigated the functional profile of CD8 T cells during primary infection.…”
Section: Discussionmentioning
confidence: 99%
“…The repertoire-wide property H Δ , as a measure of the component of CDR3 diversity most closely tied to antigen binding function, facilitates quantitative comparison between TCR repertoires. Here, we observed increasing VJ-independent diversity in the TIL repertoires-but not the matched PBMC-of patients with increasing glioma grade, suggestive of the diversified antigen targeting associated with active T-cell responses in both cancer and infectious diseases (24)(25)(26).…”
Section: −6mentioning
confidence: 82%